Structural and Functional Brain Correlates of Treatment Response in Posttraumatic Stress Disorder - Hinojosa, Cecilia. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Psychology.; Advisor: Lisa Shin.; Committee: Samuel Sommers, Elizabeth Race, and Sanne van Rooij.; Keyword: Neurosciences.